Fluid-structure interactions slender structures and axial flow - Paidoussis, M. P. (Amsterdam Academic Press, 2016)
The second of two volumes concentrating on the dynamics of slender bodies within or containing axial flow, Volume 2 covers fluid-structure interactions relating to shells, cylinders and plates containing or immersed in axial flow, as well as slender structures subjected to annular and leakage flows. This volume has been thoroughly updated to reference the latest developments in the field, with a continued emphasis on the understanding of dynamical behaviour and analytical methods needed to provide long-term solutions and validate the latest computational methods and codes, with increased coverage of computational techniques and numerical methods, particularly for the solution of non-linear three-dimensional problems.--Provided by publisher.
Includes bibliographical references and indexes.
Electronic reproduction.
Keywords: Fluid-structure interaction; Electronic books